Effect of physicochemical parameters on zooplankton in the brackish, coastal Vistula Lagoon - Ewa Paturej; Agnieszka Gutkowska; Jacek Koszałka; Magdalena Bowszys (Oceanologia)
This paper analyzes whether physicochemical properties significantly influence the occurrence of zooplankton in a brackish reservoir. The studies were carried out on the Vistula Lagoon in August and September from 2006 to 2009 at 32 research sites. The environmental conditions in the Vistula Lagoon varied widely. At the time of the investigation, 17 species of rotifers, six species of Cladocera, and ten species of Copepoda were noted, and the total density of plankton fauna ranged from 145 to 765 ind. dm−3. Statistical analysis demonstrated a significant correlation between the occurrence of some zooplankton species and certain environmental parameters, whereas the sampling sites were grouped according to study years. The zooplankton systems recorded at the research sites in 2006 constitute the most disparate group. Thus, it can be concluded that physicochemical properties might significantly impact both individual species (depending on their environmental demands) and entire zooplankton clusters.